The IFS Green Budget: October 2024 - Carl Emmerson; Paul Johnson; Kate Ogden (Institute for Fiscal Studies (IFS), 2024)
The new Chancellor faces a difficult fiscal inheritance. Her choices on tax and spending at this first Budget could define the rest of the parliament.
Keywords: 330; Government finances and spending; Health and social care; Poverty; inequality and social mobility; Savings; pensions and wealth; Taxes and benefits; Government spending; Public sector; Poverty; Social care; Tax; Fiscal rules and frameworks